Abscisic and Jasmonic Acids Contribute to Soybean Tolerance to the Soybean Aphid (Aphis glycines Matsumura). Issue 1 (December 2018) - Chapman, Kaitlin; Marchi-Werle, Lia; Hunt, Thomas; Heng-Moss, Tiffany; Louis, Joe
Abstract Plant resistance can provide effective, economical, and sustainable pest control. Tolerance to the soybean aphid has been identified and confirmed in the soybean KS4202. Although its resistance mechanisms are not fully understood, evidence suggests that enhanced detoxification of reactive oxygen species (ROS) is an active system under high aphid infestation. We further explored tolerance by evaluating the differences in constitutive and aphid-induced defenses in KS4202 through the expression of selected defense-related transcripts and the levels of the phytohormones abscisic acid (ABA), jasmonic acid (JA), JA-isoleucine (JA-Ile), cis-(+)-12-oxo-phytodienoic acid (OPDA), and salicylic acid (SA) over several time points. Higher constitutive levels of ABA and JA, and basal expression of ABA- and JA-related transcripts were found in the tolerant genotype. Conversely, aphid-induced defenses in KS4202 were expressed as an upregulation of peroxidases under prolonged aphid infestation (>7 days). Our results point at the importance of phytohormones in constitutive defense in KS4202 tolerance to the soybean aphid. Understanding the underlying mechanisms of tolerance will assist breeding for soybean with these traits, and perhaps help extend the durability ofRag (Resistance to Aphis glycines) -mediated resistance genes.